Genetic diversity in Indian mustard (Brassica juncea) genotypes for Sclerotinia stem rot (Seclerotinia sclerotiorum) using SSR markers - SINGH, MANJEET; AVTAR, RAM; SINGH, VIVEK K; MAHAVIR, MAHAVIR; KUMARI, NISHA (The Indian Journal of Agricultural Sciences, 2021)
The analysis of variance confirmed that the average sum of squares was significant for lesion length (cm). Genetic diversity as well as structure of population between genotypes of Indian mustard [Brassica juncea (L.) Czern. & Coss.] resistant to Sclerotinia stem rot [Sclerotinia selerotiorum (Lib.) de Bary] was carried out using simple sequence repeats (SSRs). A total of 114 alleles were generated via 48 polymorphic primers, with mean value of 2.38 alleles per primer. The average value of PIC and the mean gene expected heterozygosity/diversity (He) value from all the polymorphic primers were 0.43 and 0.50, respectively. All the 16 genotypes were categorized into three major clusters depending on Jaccard's dissimilarity coefficients. Evanno method for population structure revealed the presence of three populations (SP1, SP2 and SP3) at maximum ∆K. SP1 mainly comprised of resistant/highly resistant genotypes. These findings indicate the existence of ample amount of genetic variability between all the Indian mustard genotypes that could be exploited in future breeding programs to develop Sclerotinia stem rot resistant mustard cultivars.